Optional case marking in Darma (Tibeto-Burman) - Willis, Christina M. (2024)
In this paper I will explore the limitations of using a single methodology in language description and documentation. Specifically, I will argue as others have (Chelliah 2001; Sherzer 1987; Urban 1991), that multiple methods of data collection are necessary in order to adequately describe a language. To illustrate my point I will examine the distribution of ergative case marking in Darma. Described in early sketches as having a split-ergative system, I demonstrate that the pattern of distribution for the ergative morpheme is not obligatory and that it can appear in a variety of contexts that extend beyond the limits described in the split-system. Using data obtained through multiple methodologies, I show that the use of the ergative is not only optional, but its use may serve a pragmatic function that is not yet fully understood.